2022
DOI: 10.1186/s12888-022-03793-7
|View full text |Cite
|
Sign up to set email alerts
|

Incremental burden of relapse in patients with major depressive disorder: a real-world, retrospective cohort study using claims data

Abstract: Background Relapse is common in major depressive disorder (MDD). In this study, we evaluated the incremental health care burden of relapse in patients with MDD. Methods This real-world retrospective cohort study used administrative medical and pharmacy claims data to identify commercially insured adult patients in the United States diagnosed with MDD who initiated a new antidepressant between January 1, 2012, and September 30, 2017. All-cause healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The adherence rates observed in our study were similar to those established in the literature, with some variation 17–19 . In our study, the mean adherence rate of 100% or greater was observed among individuals receiving antidepressants, antipsychotics, and lithium.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The adherence rates observed in our study were similar to those established in the literature, with some variation 17–19 . In our study, the mean adherence rate of 100% or greater was observed among individuals receiving antidepressants, antipsychotics, and lithium.…”
Section: Discussionsupporting
confidence: 90%
“…The adherence rates observed in our study were similar to those established in the literature, with some variation. [17][18][19] In our study, the mean adherence rate of 100% or greater was observed among individuals receiving antidepressants, antipsychotics, and lithium. However, a majority of studies have determined that adherence to psychotropic medication is typically lower than 70%.…”
Section: Discussionmentioning
confidence: 87%
“…Still, the monoaminergic system is considered a central element in the pathogenesis of MDD, although multiple interactions with other CNS pathways are also important for the understanding of this disorder [ 72 , 73 ]. At a practical level, despite quite a large armamentarium of pharmacological agents for MDD, there is an important percentage of patients who did not reach remission or have a high relapse rate [ 74 , 75 ]. Therefore, the validation through clinical research of new treatments for MDD is paramount for the quality of life, clinical evolution, and prognosis of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a chronic disorder. A large number of patients with depression relapse [Touya et al . 2022].…”
Section: Introductionmentioning
confidence: 99%